PBL Model Based on Religious Values for the Implementation of Students’ Habits and Understanding in Grade 5 of State Elementary School Wlahar 03 - Iswatun Hasanah; Ana Andriani (Proceedings Series on Social Sciences & Humanities, 2025)
21st century education demands holistic development of students’ character, not only in cognitive aspect but also affective and psychomotor. One approach that can be used to achieve this goal is Problem Based Learning (PBL), a student-centered learning model that emphasizes solving real problems as the context of learning. This study aims to develop and analyze the implementation of PBL model integrated with religious values in order to form positive habits and improve students’ understanding of learning materials in grade V of elementary school. The research method used is classroom action research (CAR) which is carried out in two cycles, each consisting of planning, implementation, observation, and reflection stages. The subjects of this study were grade V students in one of the elementary schools in Cilacap Regency, totaling 43 students. The instruments used include student habituation observation sheets, material understanding tests, attitude questionnaires, and documentation of learning activities. The results of the study indicate that the implementation of PBL model based on religious values has a positive impact on the formation of students’ character, especially in terms of honesty, responsibility, cooperation, and caring. This habituation is naturally integrated through problem-solving scenarios that are linked to the context of daily life and religious values, such as fairness in sharing, helping each other, and respecting the opinions of others. The integration of religious values in learning not only enriches the context of problem solving, but also encourages students to reflect on their actions and thoughts in a moral and spiritual framework. Teachers play an important role as facilitators who design relevant learning scenarios, as well as being role models in implementing these values in teaching and learning activities. Thus, the PBL model based on religious values can be used as an alternative effective learning strategy to form positive habits and improve students' conceptual understanding, especially at the elementary school level. The recommendation from this study is the need for training for teachers in designing and implementing the value-integrated PBL model, as well as support from the school to create a conducive learning environment for the formation of students' character in a sustainable manner.